Hyperpolarized (3)He Diffusion MRI and Histology of Secreted Frizzled Related Protein-1 (SFRP1) Deficient Lungs in a Murine Model - Siddiqui, Sarmad (2014)
Secreted Frizzled Related Protein-1 (SFRP1) plays a key role in many diverse processes, including embryogenesis, tissue repair, bone formation, and tumor genesis. Previous studies have shown the effects of the SFRP1 gene on lung development using the SFRP1 knockout mouse model via histological and physiological studies. In this study, the feasibility of ADC (acquired via HP (3)He) to detect altered lung structure in the SFRP1 knockout (SFRP1(−/−)) mice was investigated, and compared to analysis by histology. This study consisted of two groups, the wild type (WT) mice and the knockout (KO) mice with n = 6 mice for each group. (3)He ADC MRI and histology were performed on all of the animals. The global L(m) of WT and KO mice were 35.0±0.8 μm and 38.4±3.8 μm, respectively, which translated to an increase of 9.58% in the L(m) of KO mice. The mean global ADC for the WT and KO mice were 0.12±.01 cm(2)/s and 0.13±.01 cm(2)/s, respectively, which equated to a relative increase of 8.0% in the KO mice compared to the WT mice. In the sub-xanalysis of the anterior, medial and posterior lung regions, L(m) increased by 10.50%, 6.66% and 11.84% in the KO mice, respectively, whereas the differences in ADC between the two groups in the anterior, medial, and posterior regions were 7.3%, 8.3%, and 4.6%, respectively. These results suggest that HP MRI measurements can be used as a suitable substitute for histology to obtain valuable information about lung geometry noninvasively. This technique is also advantageous as regional measurements can be performed, which can identify lung destruction more precisely. Most importantly, this approach extends far beyond the specific pathology analyzed in this study, as it can be applied to many other pathological conditions in the lung tissue, as well to many other embryonic studies.